ANALISIS SISTEM INFORMASI AKUNTANSI PENGGAJIAN DI INDUSTRI MEBEL ABC - Ade Setiawan; Helti Nur Aisyiah (Universitas PGRI Madiun, 2019)
The purpose of this study is to analyze salaries and wages system in the ABC Furniture Industry. Analysis is done by the method of Performance, Information, Economy, Control, and Efficiency (PIECES).This research used descriptive qualitative approach. The data was collected by interview, observation, and documentation. Interviews were conducted with managers, head of production, and head of finance. Observation and documentation were carried out directly at the object of research, ABC Furniture Industry.The results showed that the salaries and wages system was not fully computerized. The system has been effective in terms of performance, information, economy, security, efficiency, and service. However, there is still potential for fraud and negligence in the presence and the payment of salaries and wages is still done manually